2002
DOI: 10.1111/1467-9450.00308
|View full text |Cite
|
Sign up to set email alerts
|

Ability to take an out–group’s perspective in explaining positive and negative behaviors

Abstract: A total of 251 Latvian and Russian schoolteachers explained positive and negative behaviours from their own perspective and from the perspective of an ethnic out-group. The results were in line with the attributional pattern usually found in studies using Hewstone's direct perspective of judgement, when participants are asked to take the perspective of an ethnic out-group. That is, there was an outcome effect in causal attributions for in-group actors and a categorization effect for negative behaviour from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
(21 reference statements)
1
5
1
Order By: Relevance
“…Importantly, the behavioral expectations associated with each role-when considered independently from each other (family and business owner)-are defined by cues from the broader social context; that is, the social context sets an "identity standard" as to the behaviors appropriate for these distinct identities (Burke, 2003). While these socially ascribed standards may not be shared universally (and certainly may vary across cultures [Austers, 2002;Choi, Nisbett, & Smith, 1997]), social categories provide a comparator for behaviors and actions appropriate to a given identity. Identity conflict results when one internalizes a specific identity (i.e., family, business owner, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the behavioral expectations associated with each role-when considered independently from each other (family and business owner)-are defined by cues from the broader social context; that is, the social context sets an "identity standard" as to the behaviors appropriate for these distinct identities (Burke, 2003). While these socially ascribed standards may not be shared universally (and certainly may vary across cultures [Austers, 2002;Choi, Nisbett, & Smith, 1997]), social categories provide a comparator for behaviors and actions appropriate to a given identity. Identity conflict results when one internalizes a specific identity (i.e., family, business owner, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In a series of studies initiated at the University of Stockholm and continued at the University of Latvia, Austers, Dimdinš, and Montgomery (Austers, 2002a, 2002b; Dimdinš & Montgomery, 2004; Dimdinš, Montgomery, & Austers, 2003, 2005) extended the concepts and methods of modern social cognition research to the interethnic situation in Latvia. The concern of this team of authors was with the simultaneous and systematic investigation of several independent variables.…”
Section: Rapid and Uncontrolled Growth: Psychology In Independent Latviamentioning
confidence: 99%
“…The concern of this team of authors was with the simultaneous and systematic investigation of several independent variables. Specifically, these series of studies were focused upon student participants’ ability to adopt the out-group’s perspective in explaining instances of positive and negative behaviors and to attribute value stereotypes on the basis of group membership (Austers, 2002a, 2002b). Generally, we echo the view of Heidmets and Lauristin (2002) of Estonia that research and documentation on the Baltic experience in coping nonviolently with a difficult interethnic situation may be relevant to meting similar future challenges elsewhere.…”
Section: Rapid and Uncontrolled Growth: Psychology In Independent Latviamentioning
confidence: 99%
“…The robust nature of group differences in explaining social behavior has prompted a number of attribution studies where participants are asked to provide explanations from perspectives of other groups or individuals. A number of these studies have found that when making attributions from the imagined out-group perspective, participants simulate the out-group's motivation to have a positive and benevolent self-image, and accordingly bias their responses in favor of the out-group (Austers, 2002;Austers & Montgomery, 2001;Dimdins, Montgomery & Austers, 2003a).…”
Section: Introductionmentioning
confidence: 99%
“…In all these papers, the researchers measured the accuracy of perspective taking. This was done either on the basis of similarities in quantitative ratings provided from different perspectives (Austers, 2002;Dimdins et al , 2003a), or similarities in frequency with which certain categories of content analysis occurred in responses provided from different perspectives (Austers & Montgomery, 2001;Dimdins et al ., 2003b;Kemdal & Montgomery, 2001). It is likely that the broad theoretical and/or linguistic categories used as the measurement dimensions in these studies have failed to take into account subtler differences in the contents of behavioral explanations provided from different perspectives.…”
Section: Introductionmentioning
confidence: 99%